Análise do potencial de geração de resíduos sólidos para os municípios do sudoeste do Paraná - Crotti, Poliana Cristina (2016)
The unbridled generation of solid waste and the improperly disposal have been widely discussed, in search of the waste produced by society should be minimized and the discarded waste should be mostly recycled, causing no harm to public health or the environment. When studying solid waste, it’s necessary to take into account all aspects that interact with the very solid waste, that is, health, environmental, social, cultural and institutional aspects. The total generation of SW in Brazil in 2014 was approximately 78.6 million tons, representing an increase of 2.9% of 2013 to 2014, index higher than the population growth rate in the country in the period, which was 0 9%. Given this, the main objective of this work is to verify If the potential of solid waste generation - SW, in the municipalities of Paraná South west, relates to the socio-economic, demographic and environmental issues in 2000 and 2010. As for the method, it was used the multiple regression analysis, which is a statistical method for providing values of one or more dependent variables through a series of independent variables. It is concluded that the variable that contributed to explain the differential generation of solid waste in the municipalities of Paraná South west for the year 2000 was the GDP and GDP per capita. For the year of 2010 showed significant the same variables GDP and GDP per capita, as well as population geometric rate, reflecting government subsidies that stimulate income and consequently the marginal propensity to consume (GCMP) of the population of the cities of the South west, increasing the generation of solid waste.